Towards a Transformative Pedagogy: Improving our Education Model Using Etuaptmumk of Haudenosaunee and Western Knowledge - Maracle, Jennifer (2025)
This study uses the Two Row wampum agreement as a conceptual framework for investigating Western and Indigenous education theories. Utilizing the Etuaptmumk (Two-Eyed Seeing) approach developed by Mi’kmaw Elders Albert Marshall and Murdena Marshall, the study weaves together Indigenous and Western knowledge systems, to inform the development of a new education pedagogy that nurtures the holistic development of the whole child. The research methodology involved sharing circles with clan people from the Mohawks of the Bay of Quinte located in Kenhtè:ke Tyendinaga Mohawk Territory and integrated their understandings of the Tyonhnhéhkwen teaching and how that informs child development with Western research on education and child development. By braiding together these diverse ways of knowing, the study identified commonalities, ethical considerations, and transformative possibilities to create a new education model that address the multifaceted needs of learners within the contemporary educational landscape. This research contributes to the broader discourse on culturally responsive pedagogy, emphasizing the importance of collaborative and reciprocal approaches to education. PhD